2007
DOI: 10.1136/pgmj.2007.060244
|View full text |Cite
|
Sign up to set email alerts
|

Once weekly thyroxine treatment as a strategy to treat non-compliance

Abstract: Hypothyroidism is a common disorder, which is mainly treated in primary rather than secondary care. Once daily thyroxine replacement restores euthyroidism in most patients; some patients, however, remain hypothyroid despite adequate thyroxine replacement. Non-compliance is the most common cause of lack of response to thyroxine treatment. We describe two cases of primary hypothyroidism in which daily thyroxine treatment did not restore biochemical euthyroidism but once weekly thyroxine treatment was successful.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…A study done on Asian hypothyroid patients by Doraiswamy and Zainudin [11] demonstrated that after 3 months, there were no significant differences in thyroid profile between the weekly and daily groups. In a case series of 2 patients, Rangan et al [12] showed that once-weekly T4 is an alternative treatment strategy to treat noncompliant patients and commented that once-weekly T4 is a safe treatment regimen. However, Grebe et al [4] showed that weekly therapy was well tolerated, but TFT showed mild hypothyroidism with an increase in TSH and a decrease in T3 and T4 before the next weekly dose.…”
Section: Discussionmentioning
confidence: 99%
“…A study done on Asian hypothyroid patients by Doraiswamy and Zainudin [11] demonstrated that after 3 months, there were no significant differences in thyroid profile between the weekly and daily groups. In a case series of 2 patients, Rangan et al [12] showed that once-weekly T4 is an alternative treatment strategy to treat noncompliant patients and commented that once-weekly T4 is a safe treatment regimen. However, Grebe et al [4] showed that weekly therapy was well tolerated, but TFT showed mild hypothyroidism with an increase in TSH and a decrease in T3 and T4 before the next weekly dose.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent series evaluating hypothyroid patients with poor control have shown that adequate thyroid hormone levels were obtained after introducing weekly LT4 (17,19,20,22). However, cardiovascular side effects were not thoroughly investigated in these reports.…”
Section: Introductionmentioning
confidence: 99%
“…(25) used a small LT4 dose in an 11month old child, without initial ade quate effects on thyroid hormones levels, but reaching satisfactory thyroid hormones levels after correcting the dose by weight. In another study (19), it was also necessa ry to increase the dose for adequate control. It seems that the most adequate weekly dose is 7fold higher than the daily one.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports have suggested using a T 4 absorption test, which involves administering a bolus of 1 mg oral L-T 4 , as a strategy to identify pseudomalabsorption (12). Other reports have suggested using a bolus of weekly T 4 as a way to identify and reduce non-adherence (13). One of the earliest studies to use weekly T 4 showed that when compared with daily administration, the mean peak fT 4 following weekly administration of T 4 was significantly higher.…”
Section: Introductionmentioning
confidence: 99%